Amplification of spatial dispersion of repolarization underlies sudden cardiac death associated with catecholaminergic polymorphic VT, long QT, short QT and Brugada syndromes - ANTZELEVITCH, C. (2006)
Antzelevitch C, Oliva A (Masonic Medical Research Laboratory, Utica, NY, USA). Amplification of spatial dispersion of repolarization underlies sudden cardiac death associated with catecholaminergic polymorphic VT, long QT, short QT, and Brugada syndromes. J Intern Med 2006; 259: 48-58. This review examines the hypothesis that amplification of spatial dispersion of repolarization in the form of transmural dispersion of repolarization (TDR) underlies the development of life-threatening ventricular arrhythmias associated with inherited ion channelopathies including the long QT, short QT and Brugada syndromes as well as catecholaminergic polymorphic ventricular tachycardia. In the long QT syndrome, amplification of TDR is often secondary to preferential prolongation of the action potential duration (APD) of M cells, whereas in the Brugada syndrome, it is thought to be because of selective abbreviation of the APD of right ventricular epicardium. Preferential abbreviation of APD of either endocardium or epicardium appears to be responsible for amplification of TDR in the short QT syndrome. In catecholaminergic polymorphic VT, the reversal of the direction of activation of the ventricular wall is responsible for the increase in TDR. In conclusion, the long QT, short QT, Brugada and catecholaminergic VT syndromes are pathologies with very different phenotypes and aetiologies, but which share a common final pathway in causing sudden death.